Policy Brief : Reduction of Single-use Plastics in Vietnam - World Bank (Washington, DC : World Bank, 2022)
Vietnam is one of the world’s major plastic litter polluters; every year an estimated 280,000 to 310,000 tons of plastic leak into the ocean. The roadmap focuses on reducing the single use plastics (SUPs) polluting Vietnam’s environment such as non-degradable plastic bags; EPS food containers; plastic straws, cutlery, cups, lids, and drink stirrers; and shampoo and other toiletry bottles. The government of Vietnam has committed to banning the production and importing of plastic bags by 2026 and most single-use plastic products by 2031.